Questions d'autorité à l'école maternelle. Le petit enfant entre socialisation familiale et socialisation scolaire - Rachel Gasparini (Presses universitaires de la Méditerranée, 2012)
Changes in the nature of relationships between adults and children are feared a decline in authority. This article presents the results of sociological research conducted with twenty-three students, their parents and eight professionals (teachers, ATSEM) of nursery school who received children three years. The objective was to analyze the variations of reception and reaction to different forms of taxation in the order in which school students are more or less sensitive depending on the world around them socializing elsewhere (including family). The results presented emphasize the consideration of developments and heterogeneous characteristics of authority in the family and school discipline, to understand the unwanted behavior of some students. From this point of view, how children and adults react in the confrontation between primary socialization and secondary socialization, at a time when educational standards tend to multiply and blur the standards of behavior?